THE RELATIONSHIP BETWEEN FINANCIAL RISK MANAGEMENT AND CORPORATE RESILIENCE DURING A CRISIS: A COMPREHENSIVE LITERATURE REVIEW - Musilatin Nikmah; Hety Devita; Muhamad Eko Wahyu Umaryadi; FX. Nanang Sujatmiko (ADISAM Publisher, 2026)
This article aims to analyse the relationship between financial risk management and corporate resilience during times of crisis through a comprehensive literature review. The findings indicate that financial risk management plays a strategic role in strengthening corporate resilience, particularly through the stabilisation of cash flows, the protection of liquidity, the control of loss exposure, the improvement of decision-making quality, and the strengthening of risk governance. The literature also indicates that companies which implement integrated risk management tend to be more resilient in the face of a crisis than those which adopt a reactive or piecemeal approach to risk management. Thus, financial risk management can be understood as a vital foundation for corporate resilience, both in the short term to mitigate the impact of a crisis and in the long term to build business sustainability amidst an increasingly uncertain business environment.